CITED GENE EXPRESSION IN PAPILLARY THYROID CARCINOMA: A POTENTIAL DIAGNOSTIC MARKER - Sathler Rodrigues, Camila Bueno; Silva, Raissa Monteiro da; Pupin, Breno [UNESP]; Canevari, Renata de Azevedo (Univ Vale Paraiba-univap, 2019)
Thyroid cancer is the most common neoplasm of the endocrine system, with growing incidence in recent years. The diagnosis is performed mainly by the association of two methods: ultrasonography and fine needle aspiration (FNA); but both have a high rate of indeterminate results. Thus, it is necessary to search for alternative diagnostic methods to obtain more accurate and reliable results. Molecular biology is an area that stands out in this segment of research, aiming to understand tumor biology by the analysis of gene expression alterations. The real-time quantitative PCR (RT-qPCR) technique is a fast and efficient method of detection and quantification of gene expression, presenting high sensitivity and specificity, and being considered as a useful tool in the diagnosis of various types of cancer. In this study, samples of follicular thyroid carcinomas, papillary thyroid carcinomas, adenomatous goiter and samples of normal tissue from the gland were obtained with the objective of finding diagnostic molecular markers by evaluating the expression of genes TERT, CITED1 and SLC5A5 by RT-qPCR, that were found to be upregulated in these lesions, respectively. Significant differential expression was detected only for gene CITED1 in the comparison of the samples of papillary thyroid carcinoma with goiter and with the normal tissues, with increased expression of this gene in the papillary carcinoma samples. The results suggest gene CITED1 as a potential diagnostic marker in papillary thyroid carcinoma.
Keywords: Thyroid cancer; diagnosis; gene expression; molecular marker; gene CITED1